COX-1, COX-2 inhibitors and antifungal agents from Croton hutchinsonianus - Sirivan Athikomkulchai (2018)
Two new compounds, 3′-(4″-hydroxy-3″,5″- dimethoxyphenyl)-propyl benzoate (1) and 3′-(4″-hydroxyphenyl)- propyl benzoate (3) together with known compounds, 3′-(4″-hydroxy- 3″-methoxyphenyl)-propyl benzoate (2), poilaneic acid (4), farnesyl acetone (5) and 4-hydroxybenzaldehyde (6) were isolated and identified from the branches of Croton hutchinsonianus. Their structures were determined by spectroscopic methods. The three phenylpropyl benzoates (1-3) were found to exhibit antifungal activity against Candida albicans (IC505.36-11.41 μg/ml). Compounds 1-2 (IC502.11-4.95 μg/ml) exhibited potent but non-selective activity against the enzymes cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) whereas 3 (IC501.88 μg/ml) preferentially inhibited the enzyme COX-2. © 2006 Pharmaceutical Society of Japan.